Personalized information support for hypertension management: an open-label cluster randomized controlled trial in rural Anhui, ChinaResearch in context - Xingrong Shen; Ruirui Cui; Nana Li; Xin Yang; Tongqing Xu; Shumin Zeng; Xuanhe Liu; Yuning Wang; Ying Li; Dongying Xiao; Xuewu Zhang; Rong Liu; et al. (The Lancet Regional Health. Western Pacific)
Summary: Background: Lack of personalized hypertension management (PHM) is the main driver of low treatment and control rates of blood pressure (BP). Digital intervention has great potential in realizing PHM. Methods: This two-arm cluster randomized controlled trial aimed at assessing the added value of personalized information for leveraging commonly recognized objective behaviors facilitated by pragmatic digital applications. Implemented in Jieshou of Anhui Province, China, the intervention lasted for 12 months starting from August 2021. The primary outcome measure was systolic BP (SBP); and the secondary measures, diastolic BP (DBP), BP control rate, quality adjusted of life years (QALYs), deaths of and admissions for all-causes and hypertension complications and behavior scores. These measures were analyzed using mainly generalized linear mixed modeling controlled for clustering with or without imputation. Findings: The trial recruited 2392 patients at a response rate of 96.84%. At 12-month follow-up, the intervention group demonstrated (via intent-to treat analysis) superior SBP, −5.60 mmHg (95% CI: −8.10, −3.09; p < 0.001). Compared with 24-months follow-up, the adjusted difference decreased moderately to −3.93 mmHg (95% CI: −5.80, −2.05; p < 0.001). The intervention arm demonstrated non-greater risks of all the adverse effects observed. Interpretation: The study provides evidence to support the use of the personalized information support in controlling hypertension and its complications. The next step is an implementation strategy to incorporate the intervention into daily practice and realize its benefits. Funding: The trial was supported by National Natural Science Foundation of China (No. 72004002) and Scientific Research Foundation of Education Department of Anhui Province of China (No. KJ2021A0259).